Analysis of Irrigation Networks and Actual Operation and Maintenance Needs (AKNOP) in the Paniis Lebak Main Canal - Rico Putra Sarjono; Mohamad Riziq; Ohan Farhan (Riviera Publishing, 2026)
Irrigation network maintenance plays a strategic role in ensuring efficient and sustainable water distribution to support agricultural productivity. This study aims to evaluate the condition of the irrigation network and calculate the Actual Operation and Maintenance Needs Index (AKNOP) for the Paniis Lebak Main Canal in Kuningan Regency, West Java, Indonesia. A mixed quantitative and qualitative approach was employed through field observations, water discharge measurements, assessments of irrigation canals and hydraulic structures, and maintenance cost calculations based on the technical guidelines of the Indonesian Ministry of Public Works and Housing (PUPR). The results indicate that the irrigation canal remains generally functional; however, minor to moderate damage was identified, reducing the efficiency of water distribution. Irrigation infrastructure plays a strategic role in sustaining agricultural productivity by ensuring a reliable and well-regulated water supply to paddy fields. Optimizing the performance of the irrigation network depends largely on the effective implementation of Operation and Maintenance (O&M) activities, which must be carried out systematically and accurately. From a financial planning perspective, the Actual Operation and Maintenance Needs Index (AKNOP) serves as a critical instrument for estimating maintenance requirements. Accurate AKNOP estimation requires a comprehensive network walkthrough to identify and inventory the actual physical condition and damage of irrigation infrastructure, thereby providing a reliable basis for maintenance planning and budget allocation.